Effect of sugar cane molasses and tofu waste on the inhibitory activity of cell free fermentation broth of streptomyces antibioticus K-6 - Astrid Aulia Hamida; Noor Erma Nasution; Isnaeni Isnaeni (Universitas Ahmad Dahlan, 2019)
The use of waste as source of nutrition for human, animals, plants, and microorganism has been reported. The aim of this study was to observe the influence of sugar cane molasses (SCM) and tofu waste (TW) in various concentrations on the inhibitory effect of cell free fermentation broth (CFFB) of Streptomyces antibioticus K-6 isolated from plantation soil compare to International Streptomyces Project (ISP) standard media. The fermentation was performed in 150 rpm rotary shaker at 37ºC for five days. The inhibitory activity was investigated using diffusion agar on the nutrient agar media to determine ratio of SCM and TW by which the largest growth inhibitory zone achieved. Escherichia coli ATCC 25922 was used as a test microorganism. 10% of Streptomyces antibioticus K-6 starter was inoculated into nine compositions of SCM, TW and its combination containing media. The result indicated that SCM and TWmight be used as the component of fermentation medium of Streptomyces antibioticus K-6 for producing active metabolites. The activity of CFFB was exhibited as a diameter of growth inhibitory zone against the test bacteria; in which the largest value (24.4 mm) was detected in the combination of 0.5% SCM and 0.5% TW containig medium after two days incubation.